Assessment of the dynamics of changes in the area of water-related ecosystems: national approach - Dubianok, Sniazhana; Tavrykina Оksana; Gromadskaya, Elena; Ivashko, Egor; Makus Антон; Shpakova, Dar’ya (Journal of the Belarusian State University. Ecology, 2023)
SDG indicator 6.6.1 «Change in the extent of water-related ecosystems over time» is designed to protect the integrity of ecological functions and preserve the biodiversity of water-related ecosystems – lakes, reservoirs, rivers, flooded wetlands, etc. The development of a national methodology for assessing the dynamics of changes in the area of water-related ecosystems is due to the need to generate data on the indicator within the framework of international approaches, to create a single database for making management decisions on the conservation of fresh water and the communities of plants, animals and microorganisms interacting with it.Аccording to the concept of the international methodology, taking into account national characteristics, a project of national methodology was developed to calculate the proxy indicator 6.6.1.1 «Dynamics of changes in the area of surface water bodies», which is formed by comparing data on the area of lakes, reservoirs and rivers of the base period with the subsequent target five-year period. Based on the comparison of the base and target periods, the percentage change in spatial extent is calculated. To calculate the percentage change in spatial extent, data on the areas of lakes, reservoirs and rivers included in the Register of Surface Water Bodies of the Republic of Belarus, geoportal data on land types, certification results, cartographic calculations based on GIS, VIS and UAV own aerial photography are used. The calculation of changes in the water surface area for lakes, reservoirs, rivers was carried out. It is shown that in the study period (2018-2022), compared with the previous one (2008–2012), the water surface area of lakes (total number 2041), reservoirs (total number 84), rivers (total number 19) decreased respectively by 7,83 km2 or 0,63 %, 2,03 km2 or 0,31 %, 2,15 km2 or 0,27 %. Data, in accordance with the developed methodology, will be generated for a five-year period starting from 2023.